Prof. Conor Delaney: there’s no best technique for rectal cancer - Gao, Skylar (Annals of Laparoscopic and Endoscopic Surgery, 2017)
The 2017 Digestive Disease Institute Week (DDI Week) organized by the Cleveland Clinic was held successfully in Boca Raton, Florida, from Feb. 14th to 18th.